The Contribution of Leadership and Innovative Work Behavior (IWB) on Performance and Organizational Trust as Mediation Variable : An Empirical Study on MSMEs - Elyzabeth Wijaya (AGUSPATI Research Institute, 2023)
This study aims to analyze the relationship between the variable Leadership and organizational trust, analyze the relationship between innovative work behavior (IWB) and organizational trust, analyze the relationship between Leadership and MSME performance, analyze the relationship between innovative work behavior (IWB) and MSME performance, and analyze the relationship between organizational variables. trust on MSME performance. This type of research is quantitative associative research, namely research that aims to determine the relationship between two or more variables. The respondents of this study were 369 SMEs leaders in Jakarta who were determined by simple random sampling method. Research data was obtained by distributing questionnaires online via social media. Each research indicator was measured using a Likert scale of 1-5 points and the degree of agreement from strongly agree to strongly disagree. The analytical tool used in this research is PLS (Partial Least Square) based SEM with SmartPLS 3.0 software data processing tool. The results of the hypothesis test show that the Leadership variable has no significant effect on organizational trust, the innovative work behavior (IWB) variable has a positive and significant effect on organizational trust, the Leadership variable has a positive and significant effect on performance, the innovative work behavior (IWB) variable has a positive effect and significantly to performance, the organizational trust variable has not significant effect on MSME performance., Innovative work behaviour has no significant effect on performance through organizational trust, organizational trustdoes not mediate the relationship between Innovative work behaviour and performance.Leadership has no significant effect on performance through organizational trust, organizational trust does not mediate the relationship between Leadership on performance